Enhanching Student’s Memorization Skill of Holy Qur’an Trough the Integrated Tahfidz Program Implementation in Post Pandemic Context - Pepen Supendi; Nia Kurniawati; Muhammad Sofyan; Kresna Dewi Mulyana (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of this paper implementation of the tahfiz program in MI Terpadu Ar-Rifqi Cileunyi district for the 2020/2021 academic year; Inhibitor and backups of the tahfiz program in MI Terpadu Ar-Rifqi Cileunyi district for the 2020/2021 academic year; Tahfiz program effectiveness in improving rote at the MI Terpadu Ar-Rifqi Cileunyi district for the 2020/2021 academic year. The study involves a qualitative approach with a type of case study. The method used is a qualitative descriptive method. Data is obtained from observation, interview and documentation and then analyzed by data reductin, data display and conclusions drawing nad verification. Studies have found that include the tahfiz program goals, teachers tahfiz, tahfiz materials, tahfiz methods, memorizing the Qur’an color block, talaqqi and muraja’ah, an evaluation of daily, weekly and semester assessments and the supporting and inhibiting factors for the implementation of the tahfiz program at the MI Terpadu Ar-Rifqi. Of the increased aspects of surah that memorized by learners, the effectiveness of tahfiz programs falls into highly effective categories. According to the tahfiz materials, the effectiveness of tahfiz programs is highly ineffective.